Creativity: teaching tools for teachers - Camargo Zamata, Paulina Marisol (2017)
Creativity as a teaching strategy it is essential in all teaching work. It is one of the most original manifestations of the human being, this implies the integration of basic cognitive processes and higher cognitive processes for the achievement of new ideas, that is, the ability to analyze, assess and solve different situations that are show in the life of human being.